2023
DOI: 10.1021/acs.energyfuels.3c03037
|View full text |Cite
|
Sign up to set email alerts
|

Outlook of Cobalt-Based Catalysts for Heterogeneous Hydroformylation of Olefins: From Nanostructures to Single Atoms

Wenwen Gao,
Shihuan Liu,
Zhidong Wang
et al.

Abstract: Hydroformylation of olefins, as a study of olefinic downstream derivative production, is of great relevance in chemical production. Heterogeneous hydroformylation is beneficial for catalyst separation and recycling compared to homogeneous systems. Cobalt is a cheap metal with excellent catalytic activity in hydroformylation as well as the precious metal rhodium. Therefore, the research on cobalt-based catalysts for heterogeneous hydroformylation has great value and significance. The nano or atomic structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…The as-obtained aldehydes can serve as important intermediates for various bulk chemicals (alcohols, esters, acids, and amines). 1,2 Currently, only cobalt carbonyl and rhodium-based catalysts with phosphine ligands have been used in industry. 3 However, the difficulty in separating the products from homogeneous catalysts poses a significant obstacle to achieve efficient catalyst recovery and recycling for subsequent use.…”
Section: Introductionmentioning
confidence: 99%
“…The as-obtained aldehydes can serve as important intermediates for various bulk chemicals (alcohols, esters, acids, and amines). 1,2 Currently, only cobalt carbonyl and rhodium-based catalysts with phosphine ligands have been used in industry. 3 However, the difficulty in separating the products from homogeneous catalysts poses a significant obstacle to achieve efficient catalyst recovery and recycling for subsequent use.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Hou et al demonstrated that the incorporation of phosphorus helps to stabilize cobalt single atoms in ZrP-supported Co materials. In this regard, a recent review from from Pan et al indicated that many studies have shown that Co-based catalysts suffer from low activity and poor cycling stability, highlighting the importance of exploring new robust cobalt heterogeneous catalysts for this reaction [23].…”
Section: Introductionmentioning
confidence: 99%